2019
DOI: 10.1109/access.2019.2947765
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Measurement of Older Adults’ Mobile Device Proficiency: Results and Implications from a Study of Older Adult Smartphone Users

Abstract: Mobile device (e.g., smartphone) proficiency is becoming increasingly necessary to perform important everyday tasks, and inadequate proficiency can prevent groups of individuals such as older adults from obtaining the benefits of mobile computing and smartphone utilization. To facilitate mobile device training and research on barriers to mobile device use and adoption by older adults, Roque and Boot [1] developed the Mobile Device Proficiency Questionnaire (MDPQ). The current study is the first to assess the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Almost 90% of the participants used Android smartphones in the workshops. A study of digital inclusion for older adults showed that most participants were smartphone users, indicating that smartphones have gradually become a necessity [ 41 ], with the Android operating system considered the most prevalent among the target population of participants [ 53 ]. Most participants had healthy habits: 71.6% (58/81) practiced regular physical activity, 98.8% (78/79) were nonsmokers, and 94.9% (75/79) did not drink alcoholic beverages outside main meals.…”
Section: Resultsmentioning
confidence: 99%
“…Almost 90% of the participants used Android smartphones in the workshops. A study of digital inclusion for older adults showed that most participants were smartphone users, indicating that smartphones have gradually become a necessity [ 41 ], with the Android operating system considered the most prevalent among the target population of participants [ 53 ]. Most participants had healthy habits: 71.6% (58/81) practiced regular physical activity, 98.8% (78/79) were nonsmokers, and 94.9% (75/79) did not drink alcoholic beverages outside main meals.…”
Section: Resultsmentioning
confidence: 99%
“…Obsolete and unsupported operating systems may not be capable of incorporating these newly designed applications. Even if there are workarounds for older adults to use such applications on an obsolete device, their technological proficiency is typically lower than that of younger adults ( 34 37 ), and could limit their ability to find such solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The abbreviated (16 item) version of the MDPQ was administered which asked participants to rate their proficiency using mobile devices, including smartphones and tablet computers (e.g., “Using a mobile device I can: Send emails”). This measure has demonstrated validity and reliability ( Roque and Boot, 2018 ; Moret-Tatay et al, 2019 ; Petrovcic et al, 2019 ). The measure consists of eight subscales (subscale scores range from 1 to 5 with lower numbers representing lower proficiency).…”
Section: Methodsmentioning
confidence: 99%
“…The MDPQ was administered to understand whether technology proficiency is associated with attitudes toward wearable and mobile technologies to promote physical and cognitive health. The abbreviated (16 item) version of the MDPQ was administered which asked participants to rate their proficiency using mobile devices, including smartphones and This measure has demonstrated validity and reliability (Roque and Boot, 2018;Moret-Tatay et al, 2019;Petrovcic et al, 2019). The measure consists of eight subscales (subscale scores range from 1 to 5 with lower numbers representing lower proficiency).…”
Section: Mobile Device Proficiency Questionnairementioning
confidence: 99%